2020
DOI: 10.3390/su12124904
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Physical Activity through On-Site Quantified-Self Data Sharing

Abstract: With the development of sensing technology and the popularization of quantified-self devices, there are increasing types of health-related data that can be sensed, visualized and presented to the user. However, most existing quantified-self applications are designed to support self-management and self-reflection; only a few studies so far have investigated the social aspect of quantified-self data. In this study, we investigated the social role of quantified-self data by introducing the design and evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In addition to individual support, some wearable device applications incorporate built-in social features. Yang et al discovered that through the front display screen of SocialBike, cyclists can share competitor data, perceive the presence of rivals, and enhance their intrinsic motivation during cycling [52].…”
Section: Quantified-self and Continuance Intentionmentioning
confidence: 99%
“…In addition to individual support, some wearable device applications incorporate built-in social features. Yang et al discovered that through the front display screen of SocialBike, cyclists can share competitor data, perceive the presence of rivals, and enhance their intrinsic motivation during cycling [52].…”
Section: Quantified-self and Continuance Intentionmentioning
confidence: 99%
“…From the perspective of individual cognitive differences, scholars Li and Zhang deeply studied the psychological mechanism of the effect of the quantified self on consumers' activity participation behavior [26]. Yang (2020) and other scholars focused on the social attributes of quantified-self data and found that bicycle users can perceive the existence of competitors through competitor data-sharing while riding and can enhance the intrinsic motivation of cycling [27].…”
Section: Quantified-selfmentioning
confidence: 99%
“…Second, since the last century, KE researchers have devoted themselves to collecting and establishing massive user databases [24], which not only have the functions of storage and query but also provide data visualization, virtual product design, design scheme evaluation, and other functions [25]. Furthermore, feedback and evaluation methods of design schemes are commonly used by researchers and are continuously released to the public [26].…”
Section: Introductionmentioning
confidence: 99%